Steering magnetic coupling in diradical nonbenzenoid nanographenes - Liu, Ye; Weigold, Svenja; Yan, Linghao; Wei, Zixuan; Hanne, Malte; Tverskoy, Olena; You, Sifan; Xie, Miao; Zhang, Yanfang; Chen, Qiang; Rominger, Frank; Bunz, Uwe H. F.; et al. (Journal of the American Chemical Society, 2025)
Magnetic properties arising from controlled spin-spin interactions hold great promise for applications in spintronics and quantum technologies. In nanographenes, pentagonal and heptagonal rings introduce geometric frustration and sublattice imbalance, fundamentally altering spin localization and facilitating the emergence of open-shell structures. The precise engineering of magnetic order and coupling strength in the resulting nonbenzenoid nanographenes, however, remains a challenging and underexplored area. Here, we demonstrate an on-surface synthesis of nanographenes incorporating five- and seven-membered rings through a sequence of intramolecular C-C bond formations between methyl and aryl units. Two products are generated: the partially cyclized intermediate MAAT and the fully cyclized end product MAZC. Due to the presence of iodo groups, the resulting monomers obtained can be covalently connected via Ullmann-like coupling in variable modes, enabling programmable spin arrangements. While MAZC exists as a nonmagnetic species, MAAT featuring one seven-membered ring holds an unpaired S = 1/2 spin and exhibits Kondo resonance on a metal surface. By change of the connectivity between two MAAT units, tunable magnetic ground states and precise control over the exchange-interaction strength can be achieved. These findings, supported by scanning probe microscopy and density functional theory, establish a novel strategy for designing defined carbon nanostructures with tailored topological defects and offer fine-tuned manipulation of molecular magnetism.
Online veröffentlicht: 16. Juni 2025
Gesehen am 22.10.2025